ATTITUDE TOWARD MENTAL ILLNESS: A COMMUNITY BASED SURVEY - Talib, Uroosa; Mehmood, Nasir; Ahmed, Ashfaque; Tariq, Qudsia (Journal of Pakistan Psychiatric Society, 2024)
Background: Publics’ attitudes and approach towards mental illness highly influence their behaviors in the way they treat, support, and help a person facing challenges of mental illness.Objective: The present study envisioned to assess the literate and informally educated community person’s attitude toward mental illness and mentally ill patients in Karachi, Pakistan. Methods: The descriptive survey research design was adopted for the present study. Data was collected from various areas of Karachi city, using the attitude Scale for Mental Illness (ASMI), which has also been used in several studies worldwide. A total of 189 community-literate and informal educated people were recruited from different areas. Results: On the Separatism, Restrictiveness, and Stereotyping sub-scales, similar positive results of literate people and informal educated people agreed with the statement. Significant differences were found in the Pessimistic Prediction sub-scale. A higher percentage of informal educated people (72.5%) than literate (51.2%) felt (χ2=8.204, p<0.005). Stigmatization sub-scale: it’s a pleasant response that more than two-thirds of literate (74.1%) and informal educated people (79%) disagree. On the Benevolence sub-scale: almost half of the literate (45.6%) and more than half of informal educated community people  (61.3%) also agreed that ‘people are prejudiced towards people with mental illness’ (χ2=8.103, p<0.357).Conclusion: literate and informal educated people were showing similar positive attitudes on some subscales towards people with a mental illness but on some subscales, both groups were showing negative attitudes toward people with mental illness. There is scope for further research including examining the effects of educational interventions.